The importance of people’s awareness to donate and volunteer for the homeless in Kuala Lumpur / Raisul Faris Putra Abdul Rahman - Abdul Rahman, Raisul Faris Putra (Faculty of Art and Design, 2012)
Homelessness is a public state experienced by individuals who do not have a regular home or stable personal shelter that is warm, safe and secure. It also means not having a home. An individual does not have to be living on the streets to be homeless, even if one has a roof over their head, they can still be homeless. This may be because their home is unsuitable or they do not have any rights to stay where they live. As indicated by Gwo Burne (Masalah Gelandangan, April 2007), it is said that Kementerian Pembangunan Wanita, Keluarga dan Masyarakat has given the total of homeless in big city is as many as 7833 since 2007 to December 2011. From the research, the factors of them becoming a homeless is 46.6% jobless, 17.7 % who has low income, 10.5% old, poor and living alone, 4.8% addiction of drugs, 4.4% to those who are neglected and abandoned, 2.2% for those who have mental illness, 2.1% critical illness, 1.9% who does not have a permanent place to stay, 1.2% ex convict, 1.1% disabled, 1.0% who escaped from home, 0.6% for those who have family issues, 0.5% of depression, 0.5% of alcoholic, 0.4% refugees and 0.2% of acceptance in family. Another 1.0% remains unknown. The purpose of this study is to explore the awareness of the society to donate and to volunteer for the homeless people in Kuala Lumpur. It is argued that although providing food for them might be the right thing to do, it is also causing a lot of problems. It is how an individual takes in about an issue and whether or not they are willing to help instead of being selfish. Indepth interviews were carried out with two volunteers and another random stranger that passed by the place of distribution place. The researcher also distributed online survey through emails and social networking for the people in Kuala Lumpur area. It is found that many of people in the society are aware with the problem but as to how they reflect an issue is up to an individual. Although it is questionable whether immediate homelessness could actually be prevented, some chose that path for their life due to their lack of self esteem. This study contributes to discussions between a range of volunteers and some random strangers who are interested in the potential benefits of being aware and a help for the homeless. The first chapter will discuss about the background research. The background research will tell about the client, which is Pertiwi Soup Kitchen. Problem statement will follow in order as to state the unsolved problems about this study. Then comes the research questions, limitation, delimitation and significance of this study. Literature review would reveal on some articles and issues in Kuala Lumpur to strengthen this study.